Pengaruh Harga dan Lokasi Terhadap Keputusan Pembelian Rumah Subsidi - Aan Rahman (LPPM Universitas BSI, 2022)
The number of housing, both subsidized by the government and commercial, is an alternative choice for people today. The choice of housing is based on the community's ability to buy it in addition to the desired location and public facilities provided by the developer. This study aims to determine whether house prices and location affect the decision to purchase a house at Griya Alam Nusantara which is located on Jl. Kp. Rawajeler, Bojong Kelapa Nunggal Village, Kab. Bogor, West Java. The data used is primary data by distributing questionnaires to the owners of subsidized houses in the Griya Alam Nusantara housing estate. The population used is 200 with a sample of 67 respondents using the slovin method. Sampling technique with random sampling technique. The results of the questionnaire were processed by descriptive analysis of Validity Test, Reliability Test, Normality Test, Multiples Regression Analysis (Multiple), F Test and Regression Equation Test. The results of multiples (multiple) regression analysis are known to have Sig. (2-tailed) between the price variable (X1) and the purchasing decision variable (Y) is 0.032 <0.05, which means that there is a significant correlation between the price variable (X1) and the purchasing decision variable (Y). Value of Sig. (2-tailed) between the Location variable (X2) and the Purchasing Decision variable (Y) is 0.053 > 0.05, which means that there is no significant correlation between the Location Variable (X2) and the Purchasing Decision variable (Y). All conclusions are obtained from the regression equation test where there is an effect of Price (X1) on the Purchase Decision variable (Y) and there is no influence of the Location variable (X2) on the Purchasing Decision variable (Y) so that the first hypothesis is accepted and the second hypothesis is rejected.